Actions in practice: On details in collections. (February 2018) - Clift, Rebecca; Raymond, Chase Wesley
Several of the contributions to the Lynch et al. Special issue make the claim that conversation-analytic research into epistemics is 'routinely crafted at the expense of actual, produced and constitutive detail, and what that detail may show us'. Here, we seek to address the inappositeness of this critique by tracing precisely how it is that recognizable actions emerge from distinct practices of interaction. We begin by reviewing some of the foundational tenets of conversation-analytic theory and method – including the relationship between position and composition, and the making of collections – as these appear to be primary sources of confusion for many of the contributors to the Lynch et al. Special Issue. We then target some of the specific arguments presented in the Special Issue, including the alleged 'over-hearer's' writing of metrics, the provision of so-called 'alternative' analyses and the supposed 'crafting' of generalizations in epistemics research. In addition, in light of Lynch's more general assertion that conversation analysis (CA) has recently been experiencing a 'rapprochement' with what he disparagingly refers to as the 'juggernaut' of linguistics, we discuss the specific expertise that linguists have to offer in analyzing particular sorts of interactional detail. The article as a whole thus illustrates that, rather than being produced ' at the expense of actual, produced and constitutive detail', conversation-analytic findings – including its work in epistemics – are unambiguously anchored in such detail. We conclude by offering our comments as to the link between CA and linguistics more generally, arguing that this relationship has long proven to be – and indeed continues to be – a mutually beneficial one.